Identification of Factors Contributing to Online Game Addiction among Adolescents (Journal of Information and Communication Technology, 2021)
Nowadays, there are growing views of potentially addictive behaviors such as digital addiction, especially Online Game Addiction (OGA). This study argues that all types of addictions are related to common components, such as salience, mood modification, tolerance, withdrawal, conflict, relapse, and problems. Despite the plethora of online game consequences, there is no standard or benchmark used to classify between addicted and non-addicted users. Therefore, this study is organized to identify the factors that contribute to OGA and examine the level of OGA especially among adolescents by utilizing the Online Game Addiction Scale (OGAS). Using the same scale, the adolescents were classified into addicted and non-addicted categories. Driven by previous studies of conventional game addiction, this study adopted all the distinct common components to measure seven underlying criteria related to OGA. The dimensional structure of the scale was analyzed based on the samples of adolescents among students of higher learning institutions (HLI) in Northern Malaysia. Data were collected from 389 participants who responded to an online survey. Based on OGAS, 35 percent of the participants were found to be addicted to online games. In addition, the findings demonstrated good concurrent validity as shown by the coherent associations between the time spent on playing games and the category of the games. This study contributes to the identification of factors that influence OGA among adolescents, which are significant in preventing the occurrence of other behavioral issues such as insecure cyber and emotional behaviors.